Effects of Elastic Band Training on Body Composition and Physical Performance in Older People: A Systematic Review with Meta-Analysis - Herrera-Valenzuela, T; Cid-Calfucura, I (Elsevier Inc., 2024)
Objectives: This systematic review with meta-analysis aimed to evaluate the effects of elastic band training (EBT) on body composition and physical performance in apparently healthy older people. Methods: A systematic literature search was conducted between October 2023 and May 2024 using the core collection of six generic databases: PubMed, ProQuest, EBSCOhost, CINAHL Complete, Scopus, and Web of Science. The PRISMA, TESTEX, RoB 2, and GRADE tools assessed the evidence s methodological quality and certainty. The protocol was registered in PROSPERO (code: CRD42024547050). Results: Of 5916 records, 9 randomized and non-randomized controlled trials involving 477 healthy older people were included. Six meta-analyses were performed showing significant improvements in 30-second chair stand (SMD = 3.03; 95 % CI = 0.14 to 5.93; I2 = 100 %; p = 0.04), sit-and-reach (SMD = 2.09; 95 % CI = 0.15 to 4.03; I2 = 100 %; p = 0.04) and timed up-and-go (SMD = 3.10; 95 % CI = 1.67 to 4.53; I2 = 98 %; p < 0.0001) tests. However, in maximal isometric handgrip strength, back-scratch test, and fat-free mass, no significant improvements (p > 0.05) in favor of EBT were reported. Conclusion: EBT improves 30-second chair stand, sit-and-reach, and timed up-and-go in older people. Nevertheless, the certainty of evidence is very low; thus, not definitive recommendations can be made. © 2024 The Authors